Intimate partner violence and poor mental health among Thai women residing in Sweden - Cecilia Fernbrant; Maria Emmelin; Birgitta Essén; Per-Olof Östergren; Elizabeth Cantor-Graae (Taylor & Francis Group, 2014)
Objectives: The current aim is to examine the prevalence of intimate partner violence (IPV) among Thai women residing in Sweden and its association with mental health. We also investigate the potential influence of social isolation and social capital regarding the association between IPV and mental health outcome. Design: A public health questionnaire in Thai was distributed by post to the entire population of Thai women, aged 18-64, residing in two regions in Sweden since 2006. Items included aspects related to IPV (physical/sexual/emotional), sociodemographic background, physical health, mental health (GHQ-12), social isolation, and social capital (i.e. social trust/participation). Results: The response rate was 62.3% (n=804). Prevalence of lifetime reported IPV was 22.1%, with 20.5% by a previous partner and 6.7% by a current partner. Previous IPV exposure was significantly related to current IPV exposure, and all IPV exposure measures were significantly related to poor mental health. However, Thai women experiencing IPV by a current partner were more at risk for poor mental health than Thai women with previous or without any experience of IPV. Also, among all women exposed to IPV, those with trust in others and without exposure to social isolation seemed to have partial protection against the adverse mental health consequences associated with IPV. Conclusions: Most Thai women had never been exposed to IPV, and after migrating to Sweden, women had lower IPV exposure than in Thailand. However, the increased risk for poor mental health among those Thai women exposed to IPV suggests the need for supportive measures and targeted interventions to prevent further injuries and adverse health consequences. Although poor mental health in Thai women represents an obstacle for integration, the potential resilience indicated in the group with high social trust and without exposure to social isolation suggests that such aspects be included in the program designed to facilitate integration.